The mind of the beholder: congruence effects in luxury product placements. Issue 3 (3rd April 2023) - Rossi, Patricia; Pantoja, Felipe; Yoon, Sukki; Kim, Kacy
Abstract: This research demonstrates that viewers increase purchase intentions when they view luxury product placements in movie scenes, particularly when luxury associations are activated and when background scenes are congruent with the product's luxury image. In Study 1, participants view a luxury handbag appearing against upscale congruent or downscale incongruent backgrounds. In Study 2, participants are primed to associate with high or low social classes before they view a luxury product placed in upscale or downscale movie scenes. In Study 3, participants read a news article that describes the placed luxury product as a genuine high-end product or as a discount brand.